Pseudoaneurysm of thoracic aorta presenting as inappropriate sinus tachycardia: a case report - Azizi, Zahra (J Med Case Rep, 2019)
BACKGROUND: Pseudoaneurysm of thoracic aorta as a complication of blunt trauma to the chest, can present with a variety of symptoms due to mass compression effect. Here we report the first pseudoaneurysm of thoracic aorta presenting with chronic cough and inappropriate sinus tachycardia. The purpose of this case report is to highlight pseudoaneurysm of thoracic aorta as a rare differential diagnosis for inappropriate sinus tachycardia. CASE PRESENTATION: Here we report a case of 29-year-old white woman, a nurse, with history of a motor vehicle accident. She initially presented to medical attention with inappropriate sinus tachycardia 2 years following the motor vehicle accident during her pregnancy. Six years later she underwent sinoatrial node modification after failing a number of medications. Days prior to the ablation she developed a mild cough which became constant within a week following ablation. A computed tomography scan of her chest performed as part of a workup revealed an outpouching of the inferomedial aspect of the aortic arch, which was compressing her left main bronchus. She underwent arch repair surgery and recovered without complications. Four years later she presented with significant symptomatic sinus bradycardia requiring pacemaker placement. CONCLUSIONS: This is the first reported case of thoracic pseudoaneurysm of aorta presenting with inappropriate sinus tachycardia due to compression of the vagal nerve and cough as a result of the left main bronchus compressive effect; it highlights the importance of considering structural abnormalities in a differential diagnosis of inappropriate sinus tachycardia before any interventions.